Is Anti-NXP2 Autoantibody a Risk Factor for Calcinosis and Poor Outcome in Juvenile Dermatomyositis Patients? Case Series - Toplak, Natasa; Pimpale Chavan, Pallavi; Rosina, Silvia; Dallos, Tomas; Rotem Semo, Oz; Aguiar, Cassyanne L.; Khubchandani, Raju; Ravelli, Angelo; Patwardhan, Anjali (Frontiers in Pediatrics, 2022)
Juvenile dermatomyositis (JDM) has a wide spectrum of clinical presentations. In the last decade, several myositis-specific antibodies have been identified in patients with JDM and connected with specific organ involvement or specific clinical picture. It has been published that the presence of anti-NXP2 autoantibodies presents a risk for calcinosis in patients with JDM. We aimed to investigate the prevalence of calcinosis and response to the treatment in JDM patients with anti-NXP2. In a retrospective, multinational, multicenter study, data on 26 JDM (19 F, 7 M) patients with positive anti-NXP2 were collected. The mean age at disease presentation was 6.5 years (SD 3.7), the median diagnosis delay was four months (range 0.5-27 months). Patients were divided into two groups (A and B) based on the presence of calcinosis, which occurred in 42% of anti-NXP2 positive JDM patients (group A). Four patients already had calcinosis at presentation, one developed calcinosis after four months, and six developed calcinosis later in the disease course (median two years, range 0,8-7,8). The differences in laboratory results were not statistically significant between the groups. The mean age at disease presentation (5.2/7.5 y) was lower in group A. Children with calcinosis were treated with several combinations of drugs. In four cases, rituximab and, in one case, anti-TNF alpha agents were used successfully. Disease outcome (by evaluation of the treating physician) was excellent in four, good in two, stable in two, and poor in three patients. None of the patients from group B had a poor disease outcome. In conclusion, JDM patients with anti-NXP2 are prone to develop calcinosis, especially if they present with the disease early, before 5 years of age. The development of calcinosis is associated with worse disease outcomes. The combination of several immunomodulatory drugs and biologic drugs can stop calcinosis progression; however, there are no evidence-based therapies for treating calcinosis in JDM patients.